Proteomic characterization of extracellular vesicles produced by several wine yeast species. Issue 5 (23rd June 2020) - Mencher, Ana; Morales, Pilar; Valero, Eva; Tronchoni, Jordi; Patil, Kiran Raosaheb; Gonzalez, Ramon
Summary: In winemaking, the use of alternative yeast starters is becoming increasingly popular. They contribute to the diversity and complexity of wine sensory features and are typically used in combination with Saccharomyces cerevisiae, to ensure complete fermentation. This practice has drawn the interest on interactions between different oenological yeasts, which are also relevant in spontaneous and conventional fermentations, or in the vineyard. Although several interactions have been described and some mechanisms have been suggested, the possible involvement of extracellular vesicles (EVs) has not yet been considered. This work describes the production of EVs by six wine yeast species ( S. cerevisiae, Torulaspora delbrueckii, Lachancea thermotolerans, Hanseniaspora uvarum, Candida sake and Metschnikowia pulcherrima ) in synthetic grape must. Proteomic analysis of EV‐enriched fractions from S. cerevisiae and T. delbrueckii showed enrichment in glycolytic enzymes and cell‐wall‐related proteins. The most abundant protein found in S. cerevisiae, T. delbrueckii and L. thermotolerans EV‐enriched fractions was the enzyme exo‐1, 3‐β‐glucanase. However, this protein was not involved in the here‐observed negative impact of T. delbrueckii extracellular fractions on the growth of other yeast species. These findings suggest that EVs may play a role in fungal interactions during wine fermentation and other aspects of wine yeast biology. Abstract : This work describes the production of EVs by six wine yeast species in synthetic grape must. EVs from S. cerevisiae, and T. delbrueckii carried glycolytic enzymes and cell‐wall related proteins. The most abundant protein found in T. delbrueckii, was exo‐1, 3‐β‐glucanase, but it was not involved in its negative impact on other yeast species.